The language situation in China. - Yuming, Li (Language policies and practices in China, 2013)
China, with the world's largest population, numerous ethnic groups, and vast geographical space, is also rich in languages. Since 2006, China's State Language Commission has been publishing annual reports on ""language life"" in China. These reports cover language policy and planning, new trends in language use, and major events concerning languages in mainland China, Hong Kong, Macau, and Taiwan. Now these reports are available in English.